A COMPARATIVE ANALYTICAL STUDY OF JWARHARA KASHAYA CHOORNA AND JWARAHARA KASHAYA GHANA VATI - Meena Ramhet; Ramnani Reetesh; Sharma Amit; Yadav Sobhnath; K. Shankar Rao (International Journal of Applied Ayurved Research, 2020)
Jwarahara Kashaya Choorna is a proprietary herbal formulation, which has been under preparation for many years in NIA pharmacy and is highly effective in Fever, Joints pain etc. In the present study Jwarahara Kashaya Choorna (JKC) and its Ghana Vati (JKGV) hasbeen prepared. JKC and JKGV was evaluated on Organoleptic and physico chemical parameters. It was also tested for total microbial counts. Analytical test results showed JKC & JKGV were within normal limits but comparatively JKGV sample results was good in these perameters like Total ash, Water soluble ash, Acid insoluble ash,Water soluble extractive , Alchohal soluble extractive .Total bacterial count was little high in JKC but as in normal limits. Hence, these quality control parameters can be considered as tool for preparation of formulation.